Dendritic cells modulate burn wound healing by enhancing early proliferation. Issue 1 (19th January 2016) - Vinish, Monika; Cui, Weihua; Stafford, Eboni; Bae, Leon; Hawkins, Hal; Cox, Robert; Toliver‐Kinsky, Tracy
Abstract: Adequate wound healing is vital for burn patients to reduce the risk of infections and prolonged hospitalization. Dendritic cells (DCs) are antigen presenting cells that release cytokines and are central for the activation of innate and acquired immune responses. Studies have showed their presence in human burn wounds; however, their role in burn wound healing remains to be determined. This study investigated the role of DCs in modulating healing responses within the burn wound. A murine model of full‐thickness contact burns was used to study wound healing in the absence of DCs (CD11c promoter‐driven diphtheria toxin receptor transgenic mice) and in a DC‐rich environment (using fms‐like tyrosine kinase‐3 ligand, FL‐ a DC growth factor). Wound closure was significantly delayed in DC‐deficient mice and was associated with significant suppression of early cellular proliferation, granulation tissue formation, wound levels of TGFβ1 and formation of CD31 + vessels in healing wounds. In contrast, DC enhancement significantly accelerated early wound closure, associated with increased and accelerated cellular proliferation, granulation tissue formation, and increased TGFβ1 levels and CD31 + vessels in healing wounds. We conclude that DCs play an important role in the acceleration of early wound healing events, likely by secreting factors that trigger the proliferation of cells that mediate wound healing. Therefore, pharmacological enhancement of DCs may provide a therapeutic intervention to facilitate healing of burn wounds.